(untitled) (Anclajes, 2017)
Among the various ways of approaching the 70s in Argentina there emerges a theme which runs through a set of artistic, cinematographic and fictional narratives from the first decade of the 21st century. Their common motto could be summed up with this premise: In order to view and think about that time period in a new light, it must be divested of its familiarity, brought about by dominant memorial narratives. To grasp the extent of this method in approaching Argentina’s recent past, this article analyzes strategies of defamiliarization manifested in two ways, one literary, the other visual: the work Ezeiza paintant (MALBA 2005) by Fabian Marcaccio, and Alan Pauls’ trilogy on the 70s, especially his first two novels, Historia del llanto and Historia del pelo, which accompanied memorial debates in the beginning of 21st century in Argentina. In open dialogue with the great experimental political art of the 20th century, these works raise the issue of relations between art and history.